Pisarz i miasto : Gdańsk w prozie Stefana Chwina - Weżgowiec, Barbara (Księgarnia Akademicka Publishing, 2020)
THE CITY AND THE WRITER: GDANSK IN THE PROSE OF STEFAN CHWIN In my thesis I put together various works of Stefan Chwin, in order to follow the way how the city operates and how it becomes an important part of the story. The aim of this dissertation is to show, how the writer comprehends Gdańsk (what level of importance is given to his birthplace) and what picture of Gdańsk (along with its history, places, objects occupying the space and finally inhabitants) arises from his works. A research method is the analysis of texts and their historical-literary interpretation with regard to the cultural studies (anthropology and sociology of the literature). The basis is a specific dichotomy between the writer and the city. My study leads to the conclusions that for Chwin, Gdańsk is not only a birthplace and a place of living, but also a place that inspires. We get to know this place better and follow the history of the people that used to live here. A personal vision of the author leads to a creation of the Gdańsk (space), turning in the prose of Chwin into a specific spiritual (auto)biography of the writer.